Learning, action, and behaviour change: effective Forum Theatre design for smallholder farmers - Kirt Hainzer; Nicholas Harrigan; Van Touch; Bonny Coombe; Caitlin Finlayson; Bunnarath Som; Chariya Korn; Lita Mom; Panhaleak Chay; Pherom Song; Sao Chen; Saroeut Yong; et al. (Journal of Environmental Management, 2026)

Bridging extreme climate risks, financial precarity, and adaptation gaps: Advancing inclusive adaptation in rainfed agricultural systems - Van Touch; Ariane Utomo; De Li Liu; Nicholas Harrigan; Le-Anne Bannan; Panhaleak Chay; Caitlin Finlayson; Kirt Hainzer; Andrew McGregor; Katharine McKinnon; Lita Mom; Sophanara Phan; et al. (Global Environmental Change, 2025)

Reshaping agricultural production systems: Trade-offs and implications for sustainable intensification and environment management - Van Touch; Ariane Utomo; Nicholas Harrigan; Caitlin Finlayson; Andrew McGregor; Katharine McKinnon; Thong Anh Tran; Le-Anne Bannan; Daniel K.Y. Tan; Phan Sophanara; Panhaleak Chay; Sophea Yous; et al. (Agricultural Systems, 2025)

Agricultural extension institutions in rural Cambodia: Unpacking extension agent-farmer relations and interactions - Thong Anh Tran; Brian Robert Cook; Van Touch (Journal of Rural Studies, 2025)

Corrigendum to article title: ‘Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security’ [J. Environ. Manag., Volume: 370, Year: 2024, Pages: 122536] - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2025)

Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2024)

Adaptation constraints and prospects for future research priorities in lowland rice-based farming systems: learning experiences from Northwest Cambodia - Van Touch; Rebecca Cross; Clemens Grünbühel; Floris Van Ogtrop; Peter Ampt; Try Yorn; Robert John Martin; Brian R. Cook; Daniel K. Y. Tan (Environment, Development and Sustainability, 2023)
Sustainable agricultural development not only addresses global food insecurity but may also alleviate poverty by enriching the lives of millions of smallholder farmers. Improving the sustainability and profitability of agriculture where smallholders are dominant creates profound impacts because small landholding farmers produce approximately 70–80% of the global food. The need for a thorough understanding of the factors affecting farmers’ adoption of agricultural technologies and practices has been identified from extant literature as an important research gap. Responding to the research gap and need, this study examined the challenges that prevent farm households from adopting improved farming practices and/or technologies in Banteay Meanchey and Battambang provinces in Northwest Cambodia. A total of 524 rice producing farm household representatives were randomly selected from a household database maintained by the local government authorities. A mixed methods approach was used in the study including semi-structured interviews followed by in-depth interviews, field observations, and literature review. Farmers were found to be confronted with a range of challenges and concerns, including soil degradation, weeds, diseases, insect pests, high production costs, flooding, droughts, changing rainfall pattern, and unreliable rainfall distribution. The research findings demonstrate that improved crop production practices (e.g., adopting mechanised direct seeding methods of crop establishment, maintaining and improving soil health through crop residue retention, growing cover crops, etc.) and better resource use efficiency (e.g., reducing seeding rates to less than 100 kg/ha, being more strategic in the use of integrated nutrient, weed, and pest management strategies, etc.) can be a starting point for sustainable intensification of rice production. This transition towards intensifying paddy production sustainably may become even more effective through a clear understanding of local contexts, farm household characteristics, available resources, and the farm management practices and constraints. We observed that farmers and their associations have yet to be fully recognised as partners and actors in Cambodia. Instead, they tend to be viewed as beneficiaries and recipients of improved practices and technologies. We, therefore, propose that farmers and their associations be acknowledged and included in a process of co-creation of knowledge-practices. Such partnerships will enable the inclusion of factors (e.g., production costs, production risks, complexity and practicability of implementations, product market and prices, etc.) shown to influence farmers’ adoption of innovative farming practices and technologies. The original contribution of this article is a real-world account of the constraints and limitations experienced by smallholder rice farmers in Cambodia, which are connected to future research and development priorities in the region.

Climate change impacts on rainfed cropping production systems in the tropics and the case of smallholder farms in North-west Cambodia - Van Touch; Robert John Martin; Fiona Scott; Annette Cowie; De Li Liu (Environment, Development and Sustainability, 2017)